Effect of 5 VS 5 Small Sided Games (SSGs) Training on Passing Accuracy of U-16 Football Athletes - Gunawan; Abd Rahman (STKIP Paasundan Press, 2023)
The purpose of this study was to determine the effect of small sided games training on the passing accuracy of U-16 football athletes in Poso Regency. The method used is an experimental method with pre-test and post-test designs. Using the